Lipopolysaccharide Pre-conditioning Attenuates Pro-inflammatory Responses and Promotes Cytoprotective Effect in Differentiated PC12 Cell Lines via Pre-activation of Toll-Like Receptor-4 Signaling Pathway Leading to the Inhibition of Caspase-3/Nuclear Factor-κappa B Pathway - Sangaran, Pushpa Gandi; Ibrahim, Zaridatul Aini; Chik, Zamri; Mohamed, Zahurin; Ahmadiani, Abolhassan (Frontiers in Cellular Neuroscience, 2021)
Lipopolysacharide (LPS) preconditioning (PC), has been shown to exert protective effects against cytotoxic effects. Therefore, we hypothesised, the tolerance produced by LPS PC will be resulted by the alterations and modifications in gene and protein expression. With reference to the results of MTT assays, AO/PI staining, and Annexin V-FITC analyses of LPS concentration (0.7815-50 µg/mL) and time-dependent (12-72 hours) experiments, the pre-exposure to 3 µg/mL LPS for 12 hours protected the differentiated PC12 cells against 0.75 mg/mL LPS apoptotic concentration. LPS-treated cells secreted more inflammatory cytokines like IL-1α, IL-1β, IL-2, IL-3, IL-4, IL-6, IL-17, IFN-γ, and TNF-α than LPS-PC cells. The production of inflammatory mediators ROS and NO was also higher in the LPS-induced cells compared to LPS-PC cells. Conversely, anti-inflammatory cytokines (like IL-10, IL-13, CNTF, and IL-1Ra) were upregulated in the LPS-PC cells but not in the LPS-induced cells. Meanwhile, the LPS initiated caspase 8 which in turn activates effector caspase 3/7. When the activities of caspases in the LPS-induced cells were inhibited using z-VADfmk and z-DEVDfmk, the expressions of c-MYC and Hsp70 were increased, but p53 was reduced. The potential molecules associated with protective and destructive effect was measured by RT2 Profiler PCR array to elucidate the signaling pathways and suggested inhibition NF-κB/caspase-3 signaling pathway regulates the cytoprotective genes and proto-oncogenes. In conclusion, this study provides a basis for future research to better understand the molecular mechanism underlying LPS preconditioning/TLR4 pre-activation and its functional role in offering cytoprotective response in neuronal environment.